2018
DOI: 10.1039/c8ra00314a
|View full text |Cite
|
Sign up to set email alerts
|

Difference in the deactivation of Au catalysts during ethanol transformation when supported on ZnO and on TiO2

Abstract: Au NPs of different sizes were supported on two metal oxides: ZnO and TiO2. Differences in ethanol transformation for Au of similar particle size reveal that TiO2 support induces condensation products while ZnO only gives place to dehydrogenation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 65 publications
1
10
0
Order By: Relevance
“…These data confirm that copper-based catalysts can give rise to high yields in acetaldehyde also at high conversion, in contrast to what is mainly observed with noble metal catalysts that give rise to even 100% selectivities but only at a moderate to low conversion, while deactivation is a common problem [36].…”
Section: Ethanol To Acetaldehyde By Dehydrogenationsupporting
confidence: 77%
“…These data confirm that copper-based catalysts can give rise to high yields in acetaldehyde also at high conversion, in contrast to what is mainly observed with noble metal catalysts that give rise to even 100% selectivities but only at a moderate to low conversion, while deactivation is a common problem [36].…”
Section: Ethanol To Acetaldehyde By Dehydrogenationsupporting
confidence: 77%
“…Various catalysts for ethanol dehydrogenation have been proposed in the literature 27–37. Gold catalysts have been tested on a variety of supports such as SiO 2 27, mixed oxide ZnZrO x 28, ZnO, and TiO 2 29. These catalysts have high activity and selectivity at low temperatures and low conversion.…”
Section: Introductionmentioning
confidence: 99%
“…These catalysts have high activity and selectivity at low temperatures and low conversion. Deactivation was found due to the carbon deposition that is more pronounced for catalysts supported on TiO 2 29. Pd‐based catalysts supported on ZnO were tested in the dehydrogenation of ethanol at low temperatures with a long contact time, but a low yield of acetaldehyde was achieved 30.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that catalyst deactivation was merely motived by coke deposition, remarkably via encapsulating coke inside of the catalyst. In addition, Morales et al [17] also investigated the difference in deactivation of Au catalyst during transformation when supported on ZnO and TiO 2 . The evidence suggested that the catalyst on ZnO demonstrated higher resistance to deactivation caused by coke formation.…”
Section: Introductionmentioning
confidence: 99%